\(15^2-7xy-2y^2\)

Phân tích đa thức thành nhân tử

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

5 tháng 10 2021

\(15x^2-7xy-2y^2=15x^2-10xy+3xy-2y^2=\left(15x^2-10xy\right)+\left(3xy-2y^2\right)\)

\(=5x\left(3x-2y\right)+y\left(3x-2y\right)=\left(5x+y\right)\left(3x-2y\right)\)

26 tháng 8 2020

Bài làm:

1) Ta có: \(2x^2+5xy+2y^2\)

\(=\left(2x^2+4xy\right)+\left(xy+2y^2\right)\)

\(=2x\left(x+2y\right)+y\left(x+2y\right)\)

\(=\left(2x+y\right)\left(x+2y\right)\)

2) Ta có: \(2x^2+2xy-4y^2\)

\(=\left(2x^2-2xy\right)+\left(4xy-4y^2\right)\)

\(=2x\left(x-y\right)+4y\left(x-y\right)\)

\(=2\left(x+2y\right)\left(x-y\right)\)

26 tháng 8 2020

\(1)2x^2+5xy+2y^2=2x^2+4xy+xy+2y^2=\left(2x^2+4xy\right)+\left(xy+2y^2\right)=2x\left(x+2y\right)+y\left(x+2y\right)=\left(2x+y\right)\left(x+2y\right)\)\(2)2x^2+2xy-4y^2=2x^2+4xy-2xy-4y^2=\left(2x^2-2xy\right)+\left(4xy-4y^2\right)=2x\left(x-y\right)+4y\left(x-y\right)=\left(2x+4y\right)\left(x-y\right)\)

a) \(x^2-2x-15\)

\(\Leftrightarrow x^2-2x+1-16\)

\(\Leftrightarrow\left(x-1\right)^2-4^2\)

\(\Leftrightarrow\left(x-5\right)\left(x-3\right)\)

1 tháng 11 2018

\(a,x^2-2x-15=\left(x^2-2x+1\right)-16.\)

\(=\left(x-1\right)^2-4^2\)

\(=\left(x-5\right)\left(x+3\right)\)

2 tháng 2 2017

b) 2x^2 + 7x - 15

2x^2 + 10x - 3x -15

2x(x+5) - 3(x+5)

(x+5)(2x-3)

2 tháng 2 2017

a, 5x^3y - 10x^2y^2 + 5xy^3 = 5xy. ( x^2 - 2xy + y^2) = 5xy.( x-y)^2

b, 2x^2 + 7x -15 = 2x^2 + 10X - 3x -15

                       = 2x( x+5) - 3( x+5)

                 = ( 2x-3) (x+5) 

26 tháng 8 2020

Bài làm:

Ta có: \(2x^2-3xy-2y^2\)

\(=\left(2x^2-4xy\right)+\left(xy-2y^2\right)\)

\(=2x\left(x-2y\right)+y\left(x-2y\right)\)

\(=\left(2x+y\right)\left(x-2y\right)\)

26 tháng 8 2020

\(2x^2-3xy-2y^2\)

\(=\left(2x^2-4xy\right)+\left(xy-2y^2\right)\)

\(=2x\left(x-2y\right)+y\left(x-2y\right)\)

\(=2x\left(x-2y\right)+y\left(x-2y\right)\)

14 tháng 7 2016

\(3x^2y-5xy^2=xy\left(3x-5y\right)\).

3 tháng 11 2017

\(1-2y-y^2=1-\left(2y+y^2\right)=1-y\left(2+y\right)\)

21 tháng 1 2017

\(x^4+y^2-2x^2y+x^2+2x-2y\)

\(=\left(y^2-x^2y-xy\right)-\left(x^2y-x^4-x^3\right)+\left(xy-x^3-x^2\right)-\left(2y-2x^2-2x\right)\)

\(=y\left(y-x^2-x\right)-x^2\left(y-x^2-x\right)+x\left(y-x^2-x\right)-2\left(y-x^2-x\right)\)

\(=\left(y-x^2+x-2\right)\left(y-x^2-x\right)\)

9 tháng 8 2017

\(2x^2+4x+2-2y^2=2.\left(x^2+2x+1-y^2\right)\)\(2.\left(\left(x+1\right)^2-y^2\right)=2.\left(x+1+y\right)\left(x+1-y\right)\)

\(_{\left(-2\right)\left(y-x-1\right)\left(y+x+1\right)}\)

25 tháng 12 2016

x2-2x+1-y2+2y-1

=(x-1)2-(y2-2y+1)

=(x-1)2-(y-1)2

25 tháng 12 2016

a.)x^2-y^2-2x+2y

=(x-y)(x+y)-2(x-y)

=(x-y)(x+y-2)